Strategi Peningkatan Ekspor Kopi Indonesia di Pasar Dunia - Firmansyah, Aldi; Sugiarto, Sugiarto (Universitas Proklamasi 45, 2025)
Export is an activity that provides many benefits. One of Indonesia's leading export products is coffee; however, its exports declined from 2016 to 2021. The purpose of this study is to analyze the factors that have influenced Indonesian coffee exports from 2016 to 2021. The analysis method used in this study uses the Autoregressive Distributed Lag (ARDL) model. The results of the study show that the competitiveness of Indonesian coffee exports is weakening, but the potential for Indonesian coffee exports in 2021 tends to be better than in 2016. The variables that influence Indonesian coffee exports in the short term are the volume of Indonesian coffee exports in the previous month and the previous two months, Indonesian coffee production, world coffee prices, world tea prices, and the RCA index. While in the long term, the variables that influence the volume of Indonesian coffee exports are Indonesian coffee production, world coffee prices, world tea prices, and the RCA index. The results of the analysis also show that competitiveness is the most determining factor in increasing Indonesian coffee exports in the world market. Therefore, the government is advised to increase the competitiveness of Indonesian coffee.